2019
DOI: 10.1097/md.0000000000017859
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of cytology, thyroglobulin, and combination of them in fine-needle aspiration of metastatic lymph nodes in patients with differentiated thyroid cancer

Abstract: Background:To investigate the diagnostic performance of cytology (fine-needle aspiration cytology [FNAC]), thyroglobulin (fine-needle aspiration thyroglobulin [FNA-Tg]), and combination of them in the washout of fine-needle aspiration for those patients who have suspicious metastatic lymph nodes of differentiated thyroid cancer.Methods:Databases, including PubMed, EMbase, Web of Science and Cochrane Library were searched up to June 2019. The quality assessment of diagnostic accuracy scale-2 was used to conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…However, several studies have reported that detection of Tg in fine-needle aspiration (FNA) biopsy washout fluid from lymph nodes identifies recurrences/metastases of differentiated TC [ 38 , 39 ]. The combination of fine-needle lymph node aspiration for cytology and for thyroglobulin measurement further increases diagnostic accuracy [ 40 42 ]. Thus, in future studies ultrasound or CT guided FNA for thyroglobulin measurement and for cytology should be examined in this selected patient group.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have reported that detection of Tg in fine-needle aspiration (FNA) biopsy washout fluid from lymph nodes identifies recurrences/metastases of differentiated TC [ 38 , 39 ]. The combination of fine-needle lymph node aspiration for cytology and for thyroglobulin measurement further increases diagnostic accuracy [ 40 42 ]. Thus, in future studies ultrasound or CT guided FNA for thyroglobulin measurement and for cytology should be examined in this selected patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid follicular cells are important functional units of the thyroid gland and the place of thyroid hormone synthesis and secretion; the stability of its structure directly affects the ability of thyroid hormone synthesis and secretion [ 32 , 33 ]. We, therefore, investigated the ultrastructure changes in thyroid follicular cells under the preeclamptic status.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the T 4 and T 3 are carried by thyroxine-binding globulin (TBG) in blood, resulting in less than 0.05% of them remaining free [ 33 ]. FT 4 and FT 3 are hormones that enter target cells and bind to receptors to elicit biological effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with higher risk of recurrence should undergo follow-up examinations more frequently than the patients unlikely to develop relapse of disease. Measurement of sTg, cervical US, and occasionally whole-body scintigraphy are commonly used in the detection of metastases in patients with DTC ( 8 , 24 ).…”
Section: Discussionmentioning
confidence: 99%